A theoretical study on the proton affinity of sulfur ylides. (7th April 2022) - Yang, Yaxin; Zheng, Wenrui; Ren, Lufei; Xu, Xiaofei
Abstract : The proton affinities of sulfoxide ylides, carbonyl ylides, allyl ylides, benzenyl ylides and heterocyclic ylides with typical substituents were investigated using the SOGGA11-X functional. Abstract : Sulfur ylides have become important reagents in organic synthesis because of their unique reactivity. In this context, catalytic cyclization reactions of sulfur ylides have been well applied in organocatalytic reactions. At present, there are more and more reports on asymmetric organic catalytic reactions, and organometallic and photocatalytic reactions of sulfur ylides, which can provide more important and abundant heterocyclic compounds. During the reaction, the proton affinity (PA) can be applied to describe the nucleophilicity of sulfur ylide, which is one of the important thermodynamic properties. In our study, we first calculated the PAs of 23 sulfur ylide compounds by using theoretical methods, including five composite ab initio methods (G3, G4, G3B3, G2MP2, and G4MP2) and 26 density functional theory (DFT) methods. It was found that the SOGGA11-X functional provided the most accurate results with the smallest root-mean square error (RMSE) of 7.12 kJ mol −1 . Therefore, the PAs of sulfoxide ylides, carbonyl ylides, allyl ylides, benzenyl ylides and heterocyclic ylides with different types of substituents were studied using SOGGA11-X. The results show that the effects of different types of substituents on PA are different. In addition, natural bond orbital (NBO) and geometric conformation analyses as well as frontier orbital energy analysis were also investigated to further reveal the variation pattern of the PA values of different kinds of sulfur ylides.